2014
DOI: 10.15171/ijhpm.2014.104
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to informed consent standards in Shiraz hospitals: matrons’ perspective

Abstract: Background: Informed consent is an important part of the patients' rights and hospitals are assigned to obtain informed consent before any diagnostic or therapeutic procedures. Obtaining an informed consent enables patients to accept or reject their care or treatments and prevent future contentions among patients and medical staff. Methods: This survey was carried out during 2011-2. We assessed adherence of 33 Shiraz hospitals (governmental and non-governmental) to informed consent standards defined by Joint C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A study revealed the practice of obtaining verbal consent from mothers during procedures in postpartum care, whereas informed consent is in place for surgery, invasive procedure, anaesthesia, and using blood products 7 . Some other studies in different countries identified the non-compliance of the national standard protocols, raised ethical and legal questions, and suggested that the issue regarding respectful maternity care needs to be addressed 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study revealed the practice of obtaining verbal consent from mothers during procedures in postpartum care, whereas informed consent is in place for surgery, invasive procedure, anaesthesia, and using blood products 7 . Some other studies in different countries identified the non-compliance of the national standard protocols, raised ethical and legal questions, and suggested that the issue regarding respectful maternity care needs to be addressed 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Any examination, intervention or treatment especially for pregnant women without informed consent is considered an assault, and consent should be sought from the mother before proceeding examinations, delivery and postpartum care 4,5 . Studies conducted in health facilities worldwide indicate that women experienced some forms of disrespect or abuse, in the form of non-consented services during facility delivery and postpartum care, surgery, invasive procedure, anaesthesia, and use of blood products 6,7 . There are currently no available data on this AFFILIATION 1 BRAC, Dhaka, Bangladesh 2 icddr,b, Dhaka, Bangladesh 3 UNICEF, Dhaka, Bangladesh Assessing informed consent practices during normal vaginal delivery and immediate postpartum care in tertiary-level hospitals of Bangladesh issue in the context of Bangladesh, especially in tertiarylevel hospitals.…”
Section: Introductionmentioning
confidence: 99%